Dielectric studies of cerium doped barium titanate at different frequencies - Rahman, SN; Khatun, N; Hossain, Md Tofazzal; Khan, AH (Journal of Bangladesh Academy of Sciences, 2009)
Cerium doped barium titanate is prepared by conventional ceramic method. The dielectric studies of Ba1-x Cex TiO3 have been accomplished at room temperature over a frequency range 75 KHz to 30 MHz for x = 0.1 to 0.4 with pure BaTiO3. The measurements of the real and imaginary part of dielectric constants show strong frequency dependence. The relaxation phenomena that take place cane be attributable to the damping of dipole oscillator due to the application of external field. In the present experiment relaxation occurs at the frequency of about - 1MHZ. doi: 10.3329/jbas.v32i1.2445 Journal of Bangladesh Academy of Sciences, Vol. 32, No. 1, 79-85, 2008